Investigating Cognitive Functioning in a Sample of Spinal Cord Injury Inpatients, in Relation to the Cognitive Demands of their Specialized Rehabilitation Program: A Pilot Exploratory Study - Gray, Emma-Louise (Department of Psychology, 2023)
Spinal Cord Injury (SCI) rehabilitation programs have significant and specific cognitive demands, requiring patients to acquire knowledge and new skills while adjusting to their profoundly altered physiology. Existing research from high income countries (HIC) has shown that SCI is associated with cognitive dysfunction, which is in turn linked to poorer rehabilitation outcomes and ultimately increased costs of care. The aetiology of SCI in South Africa is distinct from HICs, which implies differences in associated risks and mediators for cognitive pathology (e.g., focal traumatic injuries, HIV-associated non-traumatic injuries), which render questionable the local generalizability of existing research evidence. There are no South African studies on cognitive dysfunction related to SCI, and research in this area from other developing world countries is sparse. Therefore, this study aimed to address the evidence gap by investigating the cognitive profile of a sample of SCI rehabilitation inpatients in relation to the cognitive demands of their SCI rehabilitation programme, at a specialized public neurorehabilitation hospital in Cape Town. This exploratory pilot study used quantitative methodology to describe the cognitive profile of a sample of new SCI rehabilitation inpatients shortly after their admission. Twentynine participants aged 18-65, who were predominantly male and from lower socioeconomic backgrounds were included in the study. All participants completed a battery of neuropsychological tests, where the assessment tools chosen measured cognitive domains identified as essential for engagement with a specialized SCI rehabilitation program. Participants also completed selected questionnaires screening for common psychological, behavioural and somatic comorbidities, with established links to cognitive dysfunction. Interpretation of the cognitive test results was undertaken through comparison with internationally and locally normed results, in conjunction with an exploration of the presence of comorbidities with known risk to cognitive function. In comparison to international data, the sample's cognitive performance was indicative of dysfunction across all domains assessed, while performance was relatively better in certain cognitive domains, relative to available South African normative data. Considering all available normative data and local trends, learning and memory, attention and certain executive functions emerged as possible areas of cognitive deficit. The potential mismatch between SCI rehabilitation programme cognitive demands and the sample's cognitive profile was evident, while their profile of comorbidities placed them at risk for cognitive dysfunction in multiple domains. This pilot study provided evidence to suggest that, despite their distinct epidemiology and lower rates of comorbid TBI, local SCI rehabilitation inpatients are at risk of cognitive dysfunction, where cognitive domains potentially affected are integral to their specialized SCI rehabilitation programme. As a pilot study conducted in the context of a pandemic, multiple areas for further investigation with altered methodology were identified. Nonetheless it was clear that additional in-depth research in this area would benefit the SCI rehabilitation community at large. Future studies should include a well-matched control group, where COVID-19 clinical research disruptions precluded this design in the current study.